Impact of climate change on the performance of cañihua production (Chenopodium pallidicaule) in the Puno Region - Benique Olivera, Eusebio (2019)
The objective of this research was to quantify the impact of climate change (temperature, precipitation and average humidity) on the yield of the production of the cañihua, agricultural campaign 1996-1997 to 2016-2017. To do this, we worked with statistical information from the Puno Regional Agrarian Directorate and the agroclimatic variables provided by the National Meteorology and Hydrology Service-Puno. The study used the method of the multiple linear regression function based on ordinary least squares to explain the yield of cañihua production under climate change conditions in the highland region. The results indicate that for each variation in a unit of the maximum temperature the yield of the cañihua increases by 3%, and for each variation in a unit of the maximum precipitation the yield increases 0.34%, for each variation in a unit of the minimum precipitation yield drops by -2.16%. While the variable maximum humidity for each variation in a unit influenced the yield in 0.70%, and the minimum humidity in 0.93%. In conclusion, cañihua maintained its production yield in the last 20 years; while rice, corn, wheat and other food grains were affected by climate change in Latin American countries and the world. The cañihua tolerated critical negative anomalies of the agroclimatic variables of the region. The high Andean grain is a food plant adaptable to climate change in the highland - Puno region.